Dykha O.V., Velboy V.P., Gedzuk T.V. Results of wear tests of of the conical standards from Steel 45 in motor oil - Диха, О.В.; Вельбой, В.П.; Гедзюк, Т.В. (Problems of Tribology, 2014)
Presented the results of tribo tests on the wear of conical standards from hard-tempered steel on the geometrical chart of tests a «cone - three balls» with lubrication. The set influence of speed of sliding and contact pressure is on intensity of wear. By mathematical two factor model of wear and got as a result of tests of its parameters the built dependences of intensity wear from determinatives.